2017
DOI: 10.1037/com0000050
|View full text |Cite
|
Sign up to set email alerts
|

Dogs’ (Canis familiaris) attention to human perception: Influence of breed groups and life experiences.

Abstract: Attending to the perception of others may help individuals gaining information from conspecifics, or help in competitive situations. Dogs (Canis familiaris) are attentive to humans' signals and their attentional state. We investigated whether dogs of different breed groups differ in their ability to pay attention to human's perception, first according to the genetic relatedness between dog breeds, and second according to working style differences. Once dogs had learned to leave forbidden food on the floor, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 40 publications
(67 reference statements)
0
19
0
Order By: Relevance
“…In contrast to herding dogs, the ancient breeds are thought to be closer genetically to wolves 7 and have not been selected specifically for human cooperation. Also, there are those breeds that are selected for hunting independently, visually separated from the owner, and that have been shown to differ in both their attention as well as behaviour towards humans 8,9 . During hunting seasons in Sweden, there is a tradition of releasing hunting dogs into the forest to let them work on their own.…”
mentioning
confidence: 99%
“…In contrast to herding dogs, the ancient breeds are thought to be closer genetically to wolves 7 and have not been selected specifically for human cooperation. Also, there are those breeds that are selected for hunting independently, visually separated from the owner, and that have been shown to differ in both their attention as well as behaviour towards humans 8,9 . During hunting seasons in Sweden, there is a tradition of releasing hunting dogs into the forest to let them work on their own.…”
mentioning
confidence: 99%
“…Previous studies have shown that dogs do not follow human misleading pointing gestures blindly (although sometimes they find them difficult to ignore [50]); instead, they can adjust their behaviour flexibly depending on the trustworthiness of the informant [51] and can discriminate between helpful and uncooperative experimenters [52]. Along this line of argument, it seems plausible to assume that dogs in royalsocietypublishing.org/journal/rspb Proc.…”
Section: Discussionmentioning
confidence: 99%
“…However, only limited attention has been devoted to the empirical investigation of dog breed differences in cognition [67]. An interesting exception is the study by Heberlein et al [68], who found that independent workers and family dogs, when forbidden to eat food, were more skilled at taking their owner's perspective than cooperative workers. Based on the results of experiment 1, we decided to compare dogs considered as cooperative workers (here: border collies) to independent workers (here: terriers) in experiment 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, cooperative worker and independent worker breeds may not actually differ in cooperativeness. Comparison of cooperative and independent dog breeds has become popular in recent years [69,81,103] but the nature of the behavioural difference that identifies one group as being more cooperative and the other group less cooperative is not clear. It is also important to highlight that cooperative and independent worker breeds were all selected to work for or with humans; thus, they could all be considered cooperative, with variation in the context in which the cooperation occurs rather than the degree of cooperativeness.…”
Section: Plos Onementioning
confidence: 99%
“…In fact, this categorization system has already elicited criticism (see, for example Udell et al [104]), particularly due to its subjectivity. The fact that differences have been found between these groups in behavioural or cognitive tasks [81,103] suggests that the distinction is meaningful in some sense but further elucidation of the differences between these breeds, and how they relate to cooperativeness, is required.…”
Section: Plos Onementioning
confidence: 99%